Investigation of the critical edge ion heat flux for L-H transitions in Alcator C-Mod and its dependence on BT. (2nd March 2018) - Schmidtmayr, M.; Hughes, J.W.; Ryter, F.; Wolfrum, E.; Cao, N.; Creely, A.J.; Howard, N.; Hubbard, A.E.; Lin, Y.; Reinke, M.L.; Rice, J.E.; Tolman, E.A.; et al.
Abstract: This paper presents investigations on the role of the edge ion heat flux for transitions from L-mode to H-mode in Alcator C-Mod. Previous results from the ASDEX Upgrade tokamak indicated that a critical value of edge ion heat flux per particle is needed for the transition. Analysis of C-Mod data confirms this result. The edge ion heat flux is indeed found to increase linearly with density at given magnetic field and plasma current. Furthermore, the Alcator C-Mod data indicate that the edge ion heat flux at the L-H transition also increases with magnetic field. Combining the data from Alcator C-Mod and ASDEX Upgrade yields a general expression for the edge ion heat flux at the L-H transition. These results are discussed from the point of view of the possible physics mechanism of the L-H transition. They are also compared to the L-H power threshold scaling and an extrapolation for ITER is given.